2010
DOI: 10.1158/1078-0432.ccr-09-3075
|View full text |Cite
|
Sign up to set email alerts
|

L1 Cell Adhesion Molecule Is a Novel Therapeutic Target in Intrahepatic Cholangiocarcinoma

Abstract: Purpose: Intrahepatic cholangiocarcinoma (ICC), a highly malignant hepatobiliary cancer, has a poor prognosis and is refractory to conventional therapies. The aim of this study is to discover a novel molecular target for the treatment of ICC.Experimental Design: To discover novel cancer-associated membrane antigens expressed in ICC cells, we generated monoclonal antibodies (mAb) by immunizing mice with intact ICC cell lines and screened for those that bind to the plasma membrane of ICC cells but not to normal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 45 publications
6
53
0
Order By: Relevance
“…In addition, biweekly intraperitoneal injection of a monoclonal L1CAM antibody (chCE7) in ovarian carcinoma-bearing mice led to significant reduction of tumor burden (45). Similar effects were recently reported using anti-L1CAM treatment in intrahepatic cholangiocarcinoma-bearing mice (46).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, biweekly intraperitoneal injection of a monoclonal L1CAM antibody (chCE7) in ovarian carcinoma-bearing mice led to significant reduction of tumor burden (45). Similar effects were recently reported using anti-L1CAM treatment in intrahepatic cholangiocarcinoma-bearing mice (46).…”
Section: Discussionsupporting
confidence: 70%
“…Min et al demonstrated in a nude mouse model with subcutaneously inoculated cholangiocarcinoma Choi-CK cells that treatment with an anti-L1CAM antibody three times per week resulted in reduced tumor outgrowth compared to therapy with a control antibody. Similar results were obtained with the cholangiocarcinoma cell line SCK in which L1CAM expression was suppressed by short hairpin RNA (shRNA) (Min et al 2010). Targeting of L1CAM using lentiviral-mediated shRNA interference in glioma tumor stem cells before injection into nude mice reduced tumor formation and prolonged survival of tumor bearing mice as well (Bao et al, 2008).…”
Section: L1cam As Target Structure In Cancer Treatment -Preclinical Rsupporting
confidence: 73%
“…Again elevated L1CAM expression conferred an apoptosis resistant phenotype even in non-tumorigenic pancreatic epithelial cells. Recent data by Min et al similarly showed that L1CAM diminished the apoptotic response of cholangiocarcinoma cells towards drug treatment with gemcitabine (Min et al, 2010). In glioblastoma stem cells, a role for L1CAM in the control of DNA damage checkpoint responses and resistance to radiotherapy has been described .…”
Section: L1cam and Apoptosis Resistancementioning
confidence: 97%
See 1 more Smart Citation
“…In particular, numerous studies have shown that forced expression of L1 in normal and cancer cell lines increases cell motility and invasiveness in vitro and in animal models in vivo. Interestingly, L1 was also shown to be aberrantly expressed in malignant tumors of the biliary tract (13,31), implying that L1 is closely associated with develop- ment and progression of biliary tract tumors. However, the exact role of L1 in GBC cells has not been previously elucidated.…”
Section: Discussionmentioning
confidence: 99%